Compensation and Incentives in Medical Networks with Gate-keeping and Case Management - Petra Schumacher (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2008)
New approaches in health care, such as e.g. Integrated Delivery Systems, affect the role and tasks of medical suppliers. More and more, medical suppliers are incorporated into the process of guiding patients to medical specialists and hospitals and thus managing the course of disease. In this context, the role of medical gate-keepers and case managers may provide opportunities for undesirable behavior (from the network's point of view). Therefore, compensation-induced incentives for gatekeepers and case managers are in the main focus of the paper. Different health care payment systems and the impact of financial and non-financial incentives on case managers and gate-keepers in medical networks are analyzed. Another focus is laid on medical suppliers that are not involved in managing diseases and guiding patients. Due to their smaller margin of actions and possibilities to take advantage of it, reimbursement should emphasize different aspects than for case managers.
urn:nbn:de:bvb:19-epub-7955-5
Keywords: I11; J33; L22; 650; networks; compensation; gate-keeping; case management